Efficiency of Governmental Funding in Hungary - Gulyás Erika; Sterbenz Tamás; Kovacs Eszter (Sciendo, 2016)
This paper presents the initial results of a significant research project conducted under the IOC PhD Student Research Grant Program with the support of the Hungarian Olympic Committee. Macro- and meso-level analyses were conducted within the framework of this research to analyze the competitive position of the Hungarian elite sport policy system. In the following, an essential part of the research will be presented with the aim of modeling the efficiency of the Hungarian sport funding system as the increasingly international sporting competition forces governments to invest more money in elite sport development just so they can maintain their elite sport success as the supply of medals remains basically constant. Due to these diminishing returns to the scale of investment, an elite sporting system with an efficient structure will be key in future sporting success. Data collection was based on information gained through a general questionnaire and interviews with the main stakeholders of national sport federations and the Hungarian Olympic Committee, which is the main governing body of Hungarian high-performance sport. Data collection focused on the sixteen prioritized sport federations and the five team sports that benefited from a tax relief system. Secondary data were collected regarding the national public funding for sport, elite sport, and sport by sport since 2006, and Gracenote's database was used to analyze historical performance in the different disciplines and compare Hungarian performance with that of other countries. This research will provide information to policy makers about the competitive position of Hungary in elite sport and, in this respect, explore the critical success factors that will allow Hungary to assess how best to manage its future success in an increasingly competitive international environment.